Respon Pemerintah Daerah Terhadap Instruksi Presiden (INPRES) No.7 Tahun 2015 Dalam Hal Peningkatan Transparansi Pengelolaan Keuangan Daerah - Rizky Zikri Sandunaez; Deviani Syafei (Universitas Negeri Padang, 2022)
This study aims to find out the response of district and city governments throughout Jambi Province to Presidential Instruction No. 7 of 2015 on Transparency of Regional Financial Information Management for fiscal year 2019-2020. The population in this study is all 11 (eleven) official websites of district and city governments throughout Jambi Province. The sampling technique used was saturated sampling technique, which is a sampling technique that uses all members of the population as a samples. The data used is secondary data in the form of data and information on regional financial management contained on the official website of district and city governments throughout Jambi Province. This study used 12 indicators requested based on Presidential Instruction No 7 of 2015. The findings showed that the response of the district city government in Jambi Province was still inadequate. The average openness index ranged from 11.8% in fiscal year 2019 and 8.93% for fiscal year 2020. Further research is expected to continue the research into a more detailed realm, such as conducting interviews and observations to find out the factors that cause the high and low level of transparency in regional financial management.